The fermion spectrum in braneworld collisions - Saffin, Paul M.; Tranberg, Anders (Springer, 2007)
In braneworld collisions fermions originally localised on one brane can be transferred to another brane, or to a space-time boundary. By modelling branes as scalar field kinks we bounce them off boundaries and study resulting effects according to a braneworld observer. Extending on our previous work, we numerically compute the spectrum of excitations of fermion modes localised on the brane and boundary, in terms of the momentum k along the brane dimensions. We find that the spectrum depends strongly on collision velocity and fermion-scalar coupling. Also, high-momentum modes tend to ``fall off'' the kinks and become delocalised radiation.